Role of foreign remittances in poverty reduction: A case of poverty-ridden Kyrgyzstan - Farrukh Nawaz Kayani (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2021)
Remittances have always been an important source of external finance for the low-income and middle-income developing countries. In Kyrgyzstan,remittances have provided a phenomenal support to the economy.The remittances from Russia to Kyrgyzstan accounted to 29 % of their GDP in 2020. There is a strong need to investigate the impact of foreign remittances upon poverty reduction for Kyrgyzstan,which is the second leading recipient country of the foreign remittances in the Central Asian region. This study has empirically investigated the impact of remittances on poverty in Kyrgyzstan by taking the variables like remittances, poverty size, capital formation, per capita GDP, savings, and unemployment for the period of 2008-2019. Ordinary least square regression was applied, and the results show an insignificant relationship between foreign remittances and poverty reduction. The reason is that remittances in Kyrgyzstan are not pro-poor as mostly the workers from the rich families have migrated to Russia.
Keywords: 330; foreign remittances; poverty reduction; Kyrgyzstan; Russia; central Asia